Linear comedo nevus. - Nicoletti, A.; Salmaso, F.; Galbiati, G.; Schiera, A.; Crippa, D.; Valente, M.G. (European Journal of Pediatric Dermatology, 2018)
A 19-year-old young woman with linear comedo nevus is reported. The disorder was first noted al the age of 8 months. lt initially affected the ulnar region of the right hand and later on the lateral aspect of the right upper limb and shoulder with a linear distribution, probably along the Blaschko's lines. From a morphological point of view, the nevus was characterized by agminated papules, with a central, dark, comedo-like horny plug. The papules, were associated with scarring residua and sebum retention cysts. The biological and radiographic examinations were within normal limits. The ophthalmological and neurological visit were negative.